Personalisation policy in the lives of people with learning disabilities: a call to focus on how people build their lives relationally. (May 2022) - Power, Andrew; Coverdale, Andy; Croydon, Abigail; Hall, Edward; Kaley, Alex; Macpherson, Hannah; Nind, Melanie
Social care provision across high-income countries has been transformed over the last ten years by personalisation – a policy agenda to give people with eligible support needs more choice and control over their support. Yet the ideological underpinnings of this transformation remain highly mutable, particularly in the context of reduced welfare provision that has unfolded in many nations advancing personalisation. How the policy has manifested itself has led to an expectation for people to self-build a life as individual consumers within a care market. This article draws on a study exploring how people with learning disabilities in England and Scotland are responding to the everyday realities of personalisation as it is enacted where they live and show the relationality inherent in their practices. We propose that the personalisation agenda as it currently stands (as an individualising movement involving an increasing responsibilisation of individuals and their families) ignores the inherently relational nature of care and support. We propose that social care policy needs to recognise the relational ways in which people build their lives and to advocate a redistribution of responsibility to reduce inequalities in the allocation of care.